Preliminary characterization of Lactobacillus salivarius K7 for probiotic properties - Narakaew, Thanrada; Pilasombut, Komkhae; Ngamyeesoon, Nualphan; Swetwiwathana, Adisorn (Asia-Pacific Journal of Science and Technology, 2017)
Lactobacillus salivarius K7 was isolated from chicken intestine. This strain produced bacteriocins against several gram-positive bacteria. Its inhibitory activities and probiotic properties were performed. Strain survival in vitro study was demonstrated in pH range of 2, 2.5, 3 and 3.5, concentrations of ox-bile at 0, 3, 6, 9 and 12%, concentrations of bile salts at 0, 0.3, 0.6 and 1%, and also fresh chicken bile in MRS at 3%. Survival of this strain in gastrointestinal tract model at pH 2, 3, 4 and 7 and cell free supernatant (CFS, pH 4) inhibitory effect on indicator strains was determined. Moreover, antibiotic resistant of this strain was examined. The results showed that Lb. salivarius K7 survived in bile salt concentration of 0, 0.3, 0.6 and 1.0% at 9.32, 2.57, 1.18 and 0.46 log cfu/ml, respectively. In addition to pH tolerant, Lb. salivarius K7 could be able to grow in culture at pH 2.5, 3 and 3.5 with viable cell count of 2.65, 7.11 and 7.23 log cfu/ml, respectively. Survival of Lb. salivarius K7 in 3% fresh chicken bile revealed slightly decreased in cell number from 9.29 to 8.03 log cfu/ml after exposed for 24 h, while this culture could tolerate to ox-bile up to 12%. This strain was completely destroyed in the presence of gastric juice at pH 2, however at pH 3 and 4 this strain survived in gastrointestinal tract model for 180 min. Antibiotic resistance properties tests showed that Lb. salivarius K7 resisted to Gentamycin, Kanamycin, Naldixic acid, Neomycin, Norfloxacin, Oxolinic acid, Tetracyclin, Oxytatracyclin and Streptomycin. This study indicated that Lb. salivarius K7 could be used as probiotic.